Spectrophotometric Determination of Nitrite using Diphenylamine as Complexing Agent - Chamsaz, Mahmoud; Hossein Arbab-Zavar, Mohammad; Akhondzadeh, Jeyran (Asian Journal of Chemistry, 2010)
A rapid, simple and sensitive method for determination of trace level of nitrite is described. Nitrite reacts with diphenylamine in sulfuric acid media with 1:2 stoichiometery and the blue coloured complex is determined at 588 nm. Beer's law is obeyed in the range of 38-1150 ng mL-1. Detection limit is 38 ng mL-1, analytical sensitivity is 6 ng mL-1 and relative standard deviation is 5 %. The effect of different ions in determination of nitrite was also investigated.